Exercise training and reproductive outcomes in women with polycystic ovary syndrome: A pilot randomized controlled trial. (3rd May 2021) - Benham, Jamie L.; Booth, Jane E.; Corenblum, Bernard; Doucette, Steve; Friedenreich, Christine M.; Rabi, Doreen M.; Sigal, Ronald J.
Abstract: Objective: Exercise is recommended for polycystic ovary syndrome (PCOS), but the most effective exercise prescription is unclear. This trial compared effects of high‐intensity interval training (HIIT), continuous aerobic exercise training (CAET) and no‐exercise control on reproductive, anthropometric and cardiometabolic outcomes in PCOS. Design: Pilot randomized controlled trial. Participants: Previously inactive women aged 18–40 years with PCOS. Measurements: Feasibility outcomes included recruitment, retention, adherence to exercise and daily ovulation prediction kit (OPK) testing. Preliminary efficacy outcomes included reproductive, anthropometric and cardiometabolic health markers. Results: Forty‐seven women were randomized to no‐exercise control ( n  = 17), HIIT ( n  = 16), or CAET ( n  = 14). Forty (85%) participants completed the trial. Median exercise adherence was 68% (IQR 53%, 86%). Median daily OPK‐testing adherence in the first half of the intervention was 87% (IQR 61%, 97%) compared with 65% (IQR 0%, 96%) in the second half. Body mass index decreased significantly in CAET compared with control (−1.0 kg/m 2, p  = .01) and HIIT (−0.9 kg/m 2, p  = .04). Mean waist circumference decreased in all groups (−7.3 cm, −6.9 cm, −4.5 cm in HIIT, CAET and control) with no significant between‐group differences. Mean LDL‐C was significantly reduced for HIIT compared to CAET (−0.33 mmol/L, p  = .03). HDL‐C increased in HIIT compared with control (0.18 mmol/L, p  = .04). Conclusions: There were feasibility challenges with adherence to daily ovulation assessment limiting the ability to analyse the effect of the exercise interventions on ovulation. CAET and HIIT were both effective at improving anthropometrics and some cardiometabolic health markers. Further studies need to determine optimal and acceptable exercise prescriptions for this population.